Recruitment of hepatic macrophages from monocytes is independent of IL‐4Rα but is associated with ablation of resident macrophages in schistosomiasis. Issue 7 (24th April 2019) - Rolot, Marion; Dougall, Annette M.; Javaux, Justine; Lallemand, François; Machiels, Bénédicte; Martinive, Philippe; Gillet, Laurent; Dewals, Benjamin G.
Abstract: Alternatively activated Mφs (AAMφ) accumulate in hepatic granulomas during schistosomiasis and have been suggested to originate in the bone marrow. What is less understood is how these Mφ responses are regulated after S. mansoni infection. Here, we investigated the role of IL‐4 receptor α‐chain (IL‐4Rα)‐signalling in the dynamics of liver Mφ responses. We observed that IL‐4Rα signalling was dispensable for the recruitment of Ly6C hi monocytes and for their conversion into F4/80 hi CD64 hi CD11b hi Mφ. Moreover, while IL‐4Rα provided an AAMφ phenotype to liver F4/80 hi CD64 hi CD11b hi Mφ that was associated with regulation of granuloma formation, it was dispensable for host survival. Resident F4/80 hi CD64 hi CD11b lo Mφ did not upregulate the AAMφ signature gene Ym1. Rather, resident Mφ nearly disappeared by week 8 after infection and artificial ablation of resident Mφ in CD169 DTR mice did not affect the response to S. mansoni infection. Interestingly, ablation of CD169 + cells in naive mice resulted in the accumulation of F4/80 hi CD64 hi CD11b hi Mφ, which was amplified when ablation occurred during schistosomiasis. Altogether, our results suggest the ablation of resident KCs after S. mansoni infection to be associated with the recruitment and accumulation of F4/80 hi CD64 hi CD11b hi Mφ with lyz2 ‐dependent IL‐4Rα contributing to the regulation of granuloma inflammation but being dispensable for host survival. Abstract : Schistosoma mansoni infection of mice induces the disappearance of CD11b lo resident macrophages and the accumulation of monocyte‐derived CD11b hi inflammatory macrophages in the liver, independently of IL‐4/13 signaling. On the other side, IL‐4/13 signaling in lyz2‐expressing cells is required for alternative activation of inflammatory macrophages and control of granulomatous inflammation.